Pengaruh Iklim Kerja dan Motivasi Kerja Terhadap Kepuasan Kerja pada Karyawan PT. Fastfood Indonesia Tbk. KFC Mataram Medan - Tiara Aulia Pratiwi; Patisina Patisina; Kaiman Turnip (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
This study aims to analyze the effect of work climate and work motivation on job satisfaction at PT. Fastfood Indonesia Tbk. KFC Mataram Medan. The hypothesis put forward is the influence of work climate and work motivation on job satisfaction. The sample in this study amounted to 102 people from a population of 102 people. The sampling technique is by using the total sample. The data collection method is the Likert scale of work climate, work motivation, and job satisfaction. Data analysis using multiple linear regression analysis model. The results of this study are: 1) There is a significant influence of work climate on job satisfaction, with a determinant coefficient value (R2) = 0.322 and p = 0.000 <0.050, meaning that the better the work climate, the higher job satisfaction. 2) There is a significant positive influence between work motivation on job satisfaction, with a determinant coefficient value (R2) = 0.303 and p = 0.000 <0.050, meaning that the better the work motivation, the higher job satisfaction. 3) There is a significant positive effect of work climate and work motivation on job satisfaction seen from the value of the determinant coefficient (R2) = 0.430 with p = 0.000 <0.050, meaning that the better the work climate and the higher the work motivation, the higher job satisfaction. Based on the results of this study the proposed hypothesis was declared accepted.